Practice of standardization of CLSI M45 A3 antimicrobial susceptibility testing of Infrequently Isolated or Fastidious Bacteria strains isolated from blood specimens in Guangdong Province 2017–2021 - He, Nanhao; Yang, Xu; Haque, Anwarul; Chen, Jiakang; Guo, Yingyi; Li, Jiahui; Yao, Likang; Zhuo, Chuyue; Wang, Jiong; Wang, Yijing; Li, Mingxin; Lin, Yexin; et al. (Frontiers in Microbiology, 2024)
The concentration of antimicrobial agents in environments like water and food has increased rapidly, which led to a rapid increase in antimicrobial resistance levels in the environment. Monitoring of bacterial resistance levels is considered as a necessary means to control the bacterial resistance. Reference standards are critical for antimicrobial susceptibility testing. CLSI M45 A3 standard defines pathogenic microorganisms that cause infections less frequently than those covered by CLSI M02, M07, and M100 as Infrequently Isolated or Fastidious Bacteria and specifies antimicrobial susceptibility testing methods. Our study investigated the epidemiology and antimicrobial susceptibility testing data of Infrequently Isolated or Fastidious Bacteria strains isolated from blood specimens in 70 hospitals in Guangdong Province between 2017 -2021. We defined testing methods other than those specified in CLSI M45 A3 as "Non-Standardized". The proportion of standardized antimicrobial susceptibility testing for penicillin increased significantly(Corynebacterium spp. 17.4 % vs 50.0 % p < 0.05；Micrococcus spp. 50.0 % vs 77.8 % p < 0.05；Abiotrophia spp. and Granulicatella spp. 21.4 % vs 90.9 % p < 0.001)， while for cefotaxime(Corynebacterium spp. 0.0 % vs 45.2 % p < 0.05； Abiotrophia spp. and Granulicatella spp. 0.0 % vs 14.3 % p = 0.515) and vancomycin increased finitely. Non-standardized methods were used for all other antimicrobials. Due to limitations in the economic and medical environment, some clinical laboratories are unable to fully comply with CLSI M45 A3 standard. We recommend that CLSI should add breakpoints for disk diffusion method to improve the standardization of antimicrobial susceptibility testing.